Quality-of-life assessment among children with esophageal achalasia - Mohamed Oulad Saiad; Mohamed Naoufal Idrissi Bahre; Noama Ryad (Wolters Kluwer Medknow Publications, 2023)
Purpose: Analyze the surgical management strategy and the current effects on Quality of Life of diagnosed Esophageal Achalasia (EA) patients in our department, with an assessment of the incidence, clinical course, and related disorders. Methods: Data was based on a retrospective review of all children who received achalasia treatment at our department between 2008 and 2022. Using the Pediatric Quality of Life Inventory Generic Core (PedsQL) Scales and the Pediatric-QL Gastrointestinal Symptoms Module (GI-PedsQL), we evaluated the long-term effects of this diagnosis on our patients' quality of life. Results: Esophageal achalasia (EA) was identified in a total of 13 cases (F: 7; M: 6). The mean patient delay was 27.90 months, and the median age was 6.5 years at diagnosis (2 months to 15 years). Regurgitation was the most frequently observed symptom, and the median follow-up was 7.32 (3- 30.7) months. There were descriptions of associations with Allgrove syndrome (n=7) and Down syndrome (n=1). All patients were treated by Open Heller myotomy (OHM) with one patient (n=1) initially treated by pneumatic dilatation (PD). In all 13 laparotomy myotomies, simultaneous fundoplication was performed using the DOR (n=12) and THAL (n=1) techniques. At follow-up, 12 patients had complete symptom relief with 1 patient exhibiting a persistence of symptoms. All 13 patients were prospectively contacted with a median time from latest check-up to date of inclusion of 2.9 (0.3-8.8) years. In comparison to data from a control group of EA patients, the overall PedsQL score of our patients was 72/100 (±17), with higher established scores in physical and emotional functioning but lower scores in social and school settings. On the other hand, when compared to a control group presenting with a gastroesophageal reflux disease (GERD), the GI-PedsQL overall score in our patients was higher with a 76/100 (±14.9), but they scored significantly lower in the dimensions: Foods and drinks limitations, difficulty swallowing, heartburn and vomiting. Discussion: Our study group's characteristics join most of the published literature with 54% of our patients presenting with Allgrove syndrome but it also joins the much rarer descriptions of Achalasia and Down's syndrome association with a singular case. The clinical course of our diagnosis process mainly consisted of timed esophagram and UGI endoscopy, lacking significantly in HREM evaluations but was efficient enough in guiding the surgical management. Our findings confirm the safety and effectiveness of Open Heller's myotomy with a success rate of 92.3% However, we concede that a laparoscopic approach should be further adopted if no contradiction is found. Moreover, we presented insight on long term QoL of patients posteriori to HM which was in concordance with other global experiences where patients reported dissatisfaction with their health and limited lifestyle. This significant negative impact was prominently present in comparison to healthy control groups as well as patients with inflammatory bowel diseases and compels a much needed discussion on the major chronic repercussions of Esophageal Achalasia in children. Conclusion: Even when managed by interdisciplinary teams of professionals, managing esophageal achalasia in specialized institutions is still a subject of debate. Early pediatric diagnosis is best achieved with routine physiological function tests and HREM. Moreover, more research is required to assess long-term Quality of Life. Standardized lifelong follow-up and qualified resources, both human and technological, are required to improve postoperative outcomes.